Building a Modern Villa Booking Platform: Vibra Information Systems Case Study - Wahyu Hidayat M; A. Muzawwirah Patawari; Surianto Mappangara; Asrafah Asrafah; Aulia Amanda Qalbi; Kasmira G; Muhammad Qalvani (Sakura Digital Nusantara, 2024)
Villa Indah Buat Rehat Anda (VIBRA) is a villa rental platform that offers a comfortable and luxurious holiday experience for customers. With a focus on reliability, performance and security, this website is designed to provide optimal service in terms of villa bookings, customer service and user satisfaction. Through data collection methods such as interviews, observations, and literature review analysis, various features and functional requirements have been determined to ensure that this website meets user needs well. In addition, defined non-functional requirements, such as data security, system availability, and ease of use, will ensure that a satisfactory and safe user experience can be achieved. Thus, the VIBRA website aims to be the main choice for those looking for quality accommodation and excellent service during their holidays.